Then and Now: Activism in Manenberg, 1980 to 2010 - Jacobs, Julian A (University of the Western Cape, 2013)
Magister Artium - MA === The study analysed the politics of resistance in Manenberg placing it within the over arching mass defiance campaign in Greater Cape Town at the time and comparing the strategies used to mobilize residents in Manenberg in the 1980s to strategies used in the period of the 2000s. The thesis also focused on several key figures in Manenberg with a view to understanding what local conditions inspired them to activism. The use of biographies brought about a synoptic view into activists lives, their living conditions, their experiences of the apartheid regime, their brutal experience of apartheid and their resistance and strength against a system that was prepared to keep people on the outside. This study found that local living conditions motivated activism and became grounds for mobilising residents to make Manenberg a site of resistance. It was easy to mobilise residents on issues around rent increases, lack of resources, infrastructure and proper housing. === South Africa